Soybean Cost-Return Budget in North Central Kansas - Lubben, Bradley D.; Staggenborg, Scott A. (My University, 2003)
This publication provides estimated cost and returns for forward farm planning for soybeans in north central Kansas.
MF2160_2003_10
Keywords: MF2160; Crops; Economics; MF